Na dnu strani? Nejezikovne prevajalske opombe v izbranih prevodih novele Balada o trobenti in oblaku Cirila Kosmača - Grošelj, Robert (Przekłady Literatur Słowiańskich, 2017)
At the Foot of the Page? Non-linguistic Translators’ Notes in Selected Translations of The Ballad of the Trumpet and the Cloud by Ciril Kosmač The translator’s notes in the Serbian, Russian, Polish, and German translations of the novella Balada o trobenti in oblaku (The Ballad of the Trumpet and the Cloud), written by a Slovenian writer, Ciril Kosmač, differ with regard to their formal and content features: the Serbian, Russian, and Polish translations contain footnotes; the German translation, on the other hand, has endnotes; content-wise, among the analysed texts, the Serbian translation occupies a special position, being the only one without the non-linguistic notes. The number of all the non-linguistic notes, explaining historical, mythological, geographical elements and everyday items, is relatively low — the Polish translation has eight such explicative notes, the Russian translation six and the German one has four; their absence in the Serbian translation may be a result of a higher socio-cultural proximity between Serbia and Slovenia in the 20th century. Despite their low number, the non-linguistic translator’s notes appear to be a very complex translation technique in the analysed translations ot Kosmač’s novella: on the one hand, they represent explanatory paratexts, added to facilitate the target reader’s comprehension of different text elements (even with a low narrative importance); on the other hand, however, they also enable the preservation of the source-text elements, contributing in such a way to the source-text orientation; translator’s notes are also a channel through which the translator and his wider socio-cultural background enter the target text in a more explicit way. The analysis of particular translations and their comparison has revealed also an intricate competition between translator’s notes and other translation techniques. Keywords: translator’s note, explicitation, translation technique, non-linguistic reality, Ciril Kosmač